Spatial Expression Analysis of Odorant Binding Proteins in Both Sexes of the Aphid Parasitoid Aphidius gifuensis and Their Ligand Binding Properties - Jiang, Xin; Qin, Yaoguo; Jiang, Jun; Xu, Yun; Francis, Frédéric; Fan, Jia; Chen, Julian (Frontiers in Physiology, 2022)
In China, Aphidius gifuensis is one of the most common endoparasitoids of green peach aphid Myzus persicae and grain aphid Sitobion miscanthi in field. Insect odorant binding proteins (OBPs) play vital roles in odor perception during feeding, host searching, mating and oviposition. In addition, some OBPs also involve in other physiological processes such as gustation and reproduction. In the present study, a comparatively antennal transcriptomic analysis was applied between male and female A. gifuensis. The spatial expression patterns among antennae, heads, thoraxes, abdomens, and legs of both sexes were further profiled. Finally, ligand binding properties of 2 OBPs (AgifOBP7 and AgifOBP9) were further evaluated. Fifteen AgifOBPs were predicted, and 14 of them were identified by gene clone, including 12 classic OBPs and 2 minus-C OBPs. As expected, all OBPs were mainly expressed with high level in antenna, head or leg which are sensory organs and tissues. Female specifically expressed AgifOBP9 displayed a broad and high binding property to aphid alarm pheromone, plant green volatiles as well as aphid sex pheromones (Ki <10 μΜ). Whereas, leg specifically expressed AgifOBP7 displays limited affinity with all tested ligands except CAU-II-11 ((E)-3,7-dimethylocta-2,6-dien-1-yl-2-hydroxy-3-methoxybenzoate), a reported EBF analogue with an exclusively high binding affinity (Ki =1.07±0.08 μΜ). The spatial expression pattern of OBPs, as well as two of their ligand binding properties revealed under our strategy lays the foundation groundwork for further functional studies of OBPs in A. gifuensis.